Monetary-crediting policy of central banks before and after COVID-19 - S. A. Andryushin (Russian Journal of Economics and Law, 2020)
Objective: to analyze the anti-inflationary policy of the leading Central banks of the world economy in 2008-2019; to explain the main postulates and discussions in the field of modern monetary theory; to show the features of the formation of anti-crisis measures and trends in the development of monetary policy of Central banks during and after COVID-19.Methods: a system-functional approach to understanding the modern monetary-credit policy of Central banks, taking into account the influence of various factors of the external and internal environment. This allowed defining and using the necessary set of specific research methods - methodological tools of historical, logical, comparative, empirical and statistical methods of knowledge.Results: the article shows that under the new financial crisis triggered by the COVID-19 pandemic, a period of active nationalization and concentration of monetary capital started in the leading countries of the world economy. Central banks are beginning to lose their operational and financial independence, and monetary issues (including credit) in the real economy are likely to be determined not by the market, but solely by the excessive needs of a sovereign government. It is noted that under the increasing sovereign debts, Central banks lose the opportunities for implementing the current anti-inflationary policy. The main elements of the modern monetary theory (MMT) are considered, as well as the features of national economies functioning within the MMT, identified by the authors of this theory.Anti-crisis measures of non-traditional monetary-credit policy were studied, which are implemented by the Central banks of the United States, Europe and Russia in the context of the COVID-19 pandemic, and their effectiveness was evaluated. In addition, a possible scenario for the development of monetary policy of Central banks after the pandemic, including the issue of digital currencies, is identified.Scientifi novelty: the article shows that massive anti-crisis measures of governments and Central banks over the next few years will provoke a global economic crisis, the main characteristics of which will be an imbalance of payment and budget systems, a rapid growth of sovereign debt, spending of economic potential by countries, and a sharp increase in infl and devaluation of national currencies. National countries will try to get out of this crisis by total digitalization of the economy, nationalization of network platforms and fi ancial assets. These processes will most likely begin with the issuance of digital currency by Central banks. Practical relevance: the main provisions and conclusions of the article can be used to specify the target mandates, tools, channels and mechanisms of Central banks’ monetary policy, directly connected with implementation of anti-recessionary measures of sovereign governments and Central banks under the COVID-19 pandemic, and with the radical digital transformation of the entire global monetary-credit system after completion of all predicted stages of the coronavirus outbreak.